Endogenous n-3 Polyunsaturated Fatty Acids Attenuate T Cell-Mediated Hepatitis via Autophagy Activation - Li, Yanli; Tang, Yuan; Wang, Shoujie; Zhou, Jing; Zhou, Jia; Lu, Xiao; Bai, Xiaochun; Wang, Xiang-Yang; Chen, Zhengliang; Zuo, Daming (Frontiers in Immunology, 2016)
Omega-3 polyunsaturated fatty acids (n-3 PUFAs) exert anti-inflammatory effects in several liver disorders, including cirrhosis, acute liver failure, and fatty liver disease. To date, little is known about their role in immune-mediated liver diseases. In this study, we used fat-1 transgenic mice rich in endogenous n-3 PUFAs to examine the role of n-3 PUFAs in immune-mediated liver injury. Concanavalin A (Con A) was administered intravenously to wild-type (WT) and fat-1 transgenic mice to induce T cell-mediated hepatitis. Reduced liver damage was shown in Con A-administrated fat-1 transgenic mice, as evidenced by decreased mortality, attenuated hepatic necrosis, lessened serum alanine aminotransferase (ALT) activity, and inhibited production of pro-inflammatory cytokines (e.g. TNF-α, IL-6, IL-17A and IFN-γ). In vivo and in vitro studies demonstrated that n-3 PUFAs significantly inhibited the activation of hepatic T cells and the differentiation of Th1 cells after Con A challenge. Further studies showed that n-3 PUFAs markedly increased autophagy level in Con A-treated fat-1 T cells compared with the WT counterparts. Blocking hepatic autophagy activity with chloroquine diminished the differences in T cell activation and liver injury between Con A-injected WT and fat-1 transgenic mice. We conclude that n-3 PUFAs limit Con A-induced hepatitis via an autophagy-dependent mechanism, and could be exploited as a new therapeutic approach for autoimmune hepatitis.